Giant mucinous cystadenocarcinoma in a young unmarried female: a case report - Sah, Ravi; Gaurav, Amrita; Qamer, Zahed A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ovarian epithelial tumours in young females are usually benign, while malignant tumours are extremely rare in this age group. Most of the tumours in young females are usually germ cell-derived. Very few cases of giant mucinous cystadenocarcinoma in young females have been reported till now. Here we present a case of a 23-year-old unmarried female with complaints of diffuse abdominal pain for 4 months and abdominal distension for 3 months. Her contrast enhanced computed tomography (CECT) abdomen was done with anill-defined large abdomino-pelvic multiloculated solid-cystic mass lesion with heterogeneously enhanced solid component measuring 21×17.4×10.1 cm, likely arising from the right adnexa. Her tumour markers were normal. The staging laparotomy was done. Intraoperatively, specimen was sent for frozen section, and the report was suggestive of mucinous cystadenocarcinoma of the ovary. This case report is aimed at showing that large ovarian masses in young females should be evaluated and that timely management should be done to improve the outcome and prognosis.